Cigarette Smoke Exposure and Inflammatory Signaling Increase the Expression of the SARS-CoV-2 Receptor ACE2 in the Respiratory Tract - Smith, Joan C.; Sausville, Erin L.; Girish, Vishruth; Yuan, Monet Lou; Vasudevan, Anand; John, Kristen M.; Sheltzer, Jason M. (Developmental cell, 2020)
The factors mediating fatal SARS-CoV-2 infections are poorly understood. Here, we show that cigarette smoke causes a dose-dependent upregulation of angiotensin converting enzyme 2 (ACE2), the SARS-CoV-2 receptor, in rodent and human lungs. Using single-cell sequencing data, we demonstrate that ACE2 is expressed in a subset of secretory cells in the respiratory tract. Chronic smoke exposure triggers the expansion of this cell population and a concomitant increase in ACE2 expression. In contrast, quitting smoking decreases the abundance of these secretory cells and reduces ACE2 levels. Finally, we demonstrate that ACE2 expression is responsive to inflammatory signaling and can be upregulated by viral infections or interferon treatment. Taken together, these results may partially explain why smokers are particularly susceptible to severe SARS-CoV-2 infections. Furthermore, our work identifies ACE2 as an interferon-stimulated gene in lung cells, suggesting that SARS-CoV-2 infections could create positive feedback loops that increase ACE2 levels and facilitate viral dissemination. [Display omitted] •Lung ACE2 levels do not vary by age or sex, but smokers exhibit upregulated ACE2•ACE2 is expressed in several lung cell types, including the secretory lineage•Chronic smoking triggers the expansion of ACE2+ secretory cells•ACE2 is also upregulated by viral infections and interferon exposure Smith et al. report that smokers’ lungs harbor higher levels of the coronavirus receptor ACE2. They further demonstrate that ACE2 is expressed in a subpopulation of secretory cells that expand in response to smoke exposure. Finally, they establish that ACE2 is an interferon-stimulated gene that is upregulated by viral infections.